The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1071/sr10159
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community and ecotoxicity analysis of bioremediated, weathered hydrocarbon-contaminated soil

Abstract: Bioremediated soils are usually disposed of after meeting legislated guidelines defined by chemical and ecotoxicity tests. In many countries including Australia, ecotoxicity tests are not yet mandatory safety requirements. This study investigated the biotreatment of weathered hydrocarbon-contaminated soils in 12-week laboratory-based microcosms. Monitored natural attenuation resulted in ~43% reduction of total petroleum hydrocarbon contaminant to 5503 mg/kg (C16–C35), making the soil suitable for disposal as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Germination assays R. sativus L. seeds (radish) were used in the germination tests to evaluate the remediation of treated soils (Sheppard et al, 2011) and studies of waste phytotoxicity (Andreozzi et al, 2008).…”
Section: Characteristics Of Parameters In Soil Solutionmentioning
confidence: 99%
“…Germination assays R. sativus L. seeds (radish) were used in the germination tests to evaluate the remediation of treated soils (Sheppard et al, 2011) and studies of waste phytotoxicity (Andreozzi et al, 2008).…”
Section: Characteristics Of Parameters In Soil Solutionmentioning
confidence: 99%
“…One of these alternate methods is termed bioaugmentation: in this case the addition of hydrocarbon degraders (mostly bacteria and to a lesser extent fungi) which are generally isolated or enriched in the laboratory from samples taken from contaminated sites (Perelo 2010 ;Sarkar et al 2005 ). Although the application of bioaugmentation to environments contaminated with petrogenic hydrocarbons has been extensively studied in both marine and terrestrial systems (Kadali et al 2012 ;Makadia et al 2011 ;Sheppard et al 2011 ;Simons et al 2012 ;, there exists potential question or concern relating to the introduction of exogenous organisms and the potential negative impacts of this introduction on the diversity and functionality of the natural ecosystem (Iwamoto and Nasu 2001 ).…”
Section: Bioaugmentation Strategymentioning
confidence: 99%
“…Using previously bioremediated soils which usually have enhanced microbial degrading capacity should be beneficial to the oil tank bottom degradation. Recent reports Sheppard et al 2011) have shown that under conditions of monitored natural attenuation, such soils were as equally effective as the application of microbe-nutrient formulation for TPH reduction in contaminated soils. The use of the fungus nutrient formulation and previously bioremediated (treated) waste soil was beneficial to TPH reduction in this study especially between days 0 and 49.…”
Section: Microbial Community Analysesmentioning
confidence: 99%
“…TPH contents of replicate samples were determined in samples using the modified standard protocol of International Organization for Standardization (ISO2004), ISO/DIS 16703 GC. The soil TPH content was estimated as described by Sheppard et al (2011). Standard calibration curves were made from hydrocarbon mixture (RTW solution) dilutions.…”
Section: Field-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation